Penerapan Model Pembelajaran Mind Mapping Guna Meningkatkan Hasil Belaar IPS - Sudirah Sudirah (JURNAL GLOBAL EDUKASI, 2021)
Abstract: In general, classroom action research aims to improve the quality of learning for grade VI students at SDN 013845 Lestari. specifically aims to: 1. Improve Student Learning Achievement; 2. Describe the management of Social Science Lessons; 3. Through Mind Mapping Learning Model with Material Appearance of Nature and Social Condition of Neighboring Countries. This classroom action research was conducted in 2 cycles, each cycle consisting of planning, acting, observing and reflecting. The classroom action research was carried out in class VI SDN 013845 Lestari, amounting to 29 students. The subjects of this study were sixth grade social science teachers and sixth grade students at SDN 013845 Lestari. Data were collected through observation, interviews, tests, and study documentation. The learning outcomes in the first cycle reached an average value of 77.33% after the first cycle and the second cycle, the reflection and recommendation values reached an average of 85.3%, meaning there was an increase of 9.97%. Keywords: mind mapping; natural appearance; neighboring countries' social conditions  Abstrak: Penelitian tindakan kelas secara umum bertujuan untuk meningkatkan kualitas pembelajaran untuk peserta didik kelas VI SDN 013845 Lestari. secara khusus bertujuan untuk: 1. Meningkatkan Prestasi Belajar Siswa; 2. Mendeskripsikan pengelolaan Pelajaran Ilmu Pengetahuan Sosial; 3. Melalui Model Pembelajaran Mind Mapping Dengan Materi Kenampakan Alam dan Keadaan Sosial Negara-negara Tetangga. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus, setiap siklus terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Penelitian tindakan kelas dilaksanakan di kelas VI SDN 013845 Lestari yang berjumlah 29 orang siswa. Subjek penelitian ini adalah guru Ilmu Pengetahuan Sosial kelas VI dan siswa kelas VI SDN 013845 Lestari, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Hasil belajar pada siklus I mencapai nilai rata-rata 77.33% setelah siklus I dan siklus II, refleksi dan rekomendasi nilai rata-rata mencapai 85.3% berarti ada peningkatan sebesar 9.97%. Kata Kunci: keadaan sosial negara tetangga; kenampakan alam; mind mapping